Drobtinice iz geoučilnice - Drnovšek, Igor (Geografski obzornik, 1997)
The article deals with the make out of some teaching aids for topics, closely linked with geology, geomorphology and cartography.
Keywords: fizična geografija; geologija; geomorfologija; kartografija; metodika pouka; učila; zemljevidi